The Philosophy of Electronic Word of Mouth and Consumer Buying Behavior in Modern Era - Rafi, Arslan; Khan , Ali Junaid; Gill, Shahzad Ali; Imdadullah, Muhammad (iRASD Journal of Economics, 2021)
Electronic word of mouth (eWoM) is gaining a lot of importance during this era of digitalization. The aim of this study is to explore how different dimensions of eWoM are translated through the biases that are a component of each individual consumer’s mindset and psychology, eventually resulting in a positive or negative purchase behaviour by the consumer. There has been a lot of literature related to the basic model of communication in a marketing context. In most of the studies of the communication model, the characteristics of the sender and the channel have been explored, but the receiver dynamics still remain a relatively less explored area of the marketing communication literature. Data was collected through a Google Doc-based questionnaire. An encouraging response of 81% was received from the respondents. Before examining the final procedures of analysis, reliability and validity are established through Cronbach’s Alpha, discriminant and convergent validities. Results show that eWoM has a strong impact on consumer buying behavior. Lastly, our results indicate that consumer bias moderates the relationship between eWoM and consumer buying behaviours. There are several practical implications of this research study. Brands must practice marketing strategies that enable value creation, which ultimately results in positive eWoM.